STUDI EKSPERIMENTAL MODEL PEMBELAJARAN HYPNOTEACHING TERHADAP HASIL BELAJAR KOSAKATA BAHASA INGGRIS PESERTA DIDIK - Natalia Tri Astuti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
The aim of this research is to know the effect of hypnoteaching learning model towards the learning result of students English vocabulary in Yadika 4 Junior High School Bekasi. The research method was experiment method. The research population was all class VIII students in Yadika 4 junior high school, and the samples was 40 students taken by random sampling which is 20 students for control class and 20 students for experiment class. According to the research result used “t” test with significant value 0,05, the test result is there is a good influence of used hypnoteaching learning model towards to result of student’s English vocabulary in Yadika 4 junior high school Bekasi.Keywords: hypnoteaching Learning Model, English Vocabulary